2014
DOI: 10.1093/jnci/dju164
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Study of Accelerated Hypofractionated Three-Dimensional Conformal Radiotherapy for Stage T1-3 N0 M0 Non-Small Cell Lung Cancer: NCIC CTG BR.25

Abstract: Conformal radiotherapy to a dose of 60 Gy in 15 fractions resulted in favorable primary tumor control and overall survival rates in patients with T1-3 N0 M0 NSCLC. Severe toxicities were uncommon with this relatively simple treatment technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 11 publications
2
35
0
Order By: Relevance
“…However, our data confirmed that the dominant pattern of relapse in these large tumours is not connected with local failure, as was similarly reported by other authors in both SBRT 24 and hypofractionated studies. 13 However, large tumours were associated with poorer rates of OS, TTP, RF and TTM. Thus, these findings suggest that systemic therapy could be an option for large tumours with concurrent hypofractionated RT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, our data confirmed that the dominant pattern of relapse in these large tumours is not connected with local failure, as was similarly reported by other authors in both SBRT 24 and hypofractionated studies. 13 However, large tumours were associated with poorer rates of OS, TTP, RF and TTM. Thus, these findings suggest that systemic therapy could be an option for large tumours with concurrent hypofractionated RT.…”
Section: Discussionmentioning
confidence: 99%
“…The National Cancer Institute of Canada (NCIC) Clinical Trials Group BR 35 study 13 revealed a 2-year tumour control rate of 87.4% and a 2-year OS of 68.7% after delivering 60 Gy in 15 fractions using 3D for peripherally located tumours ,5 cm and with Stages T1-3 N0 M0 NSCLC. Furthermore, the Cancer and Leukemia Group B (CALGB) 39904 trial 11 in a Phase I study comprised 39 patients with NSCLC T1-2 N0 M0 ,4 cm, who were treated with increasing hypofractionated RT to a total dose of 70 Gy and with reduced number of fractions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Cancer and Leukemia Group B (CALGB) trial 39904 prospectively evaluated accelerated three-dimensional conformal radiation therapy for delivery of 70 Gy in 17-29 fractions for early stage NSCLC and reported a median survival of 38.5 months and disease relapse rate of 25.6% [12]. A Canadian multi-institutional prospective phase II trial reported very promising 2-year LC rates of 87.4% following 60 Gy in 15 fractions [13]. The largest retrospective Canadian study reported a 2-year LC rate of 76.2% in 118 patients following a total dose of 48-60 Gy in 12-15 fractions, in which most patients received 48 Gy (59.7%) or 52 Gy (37.1%) [8].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that 60 Gy in 15 fractions can provide excellent local control with minimal toxicity in patients with biopsy-proven T1-3 N0 M0 NSCLC. 22 Palliative Care Studies from Europe as well as the United States have documented a single RT fraction is equivalent to multiple fractions in the treatment of bony metastatic disease. 2,23,24 Unfortunately, despite the data, single-fraction RT is still underutilized in the United States.…”
Section: Lung Cancermentioning
confidence: 99%